EKSISTENSI PENGADILAN NEGERI DALAM PENYELESAIAN SENGEKETA ADAT DI BALI - Mita Dwijayanti (Res Judicata, 2019)
Customary disputes are part of customary conflicts, whether the subjects are individuals or groups of people as a community, known as indigenous peoples in the form of traditional banjars. Based on article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) that the Indonesian nation is a rule of law, the consequence of a rule of law in Indonesia is that everything must be regulated in law. The enactment of written law in Indonesia causes the recognition of the rights of indigenous peoples in Indonesia to be recognized in writing in the Constitution, namely Article 18 B of the 1945 Constitution. If referring to article 18B paragraph (2) which formulates "the State recognizes and respects traditional law units along with their traditional rights as long as they are still alive and in accordance with the development of society and the principles of the unitary state of the Republic of Indonesia, which are regulated by Law then basically customary law community unit is a legal subject that can carry out legal actions. The ability to carry out legal actions by indigenous peoples has an impact on the legal consequences.